2014
DOI: 10.5194/acp-14-1423-2014
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol yields of 12-carbon alkanes

Abstract: Secondary organic aerosol (SOA) yields were measured for cyclododecane, hexylcyclohexane, n-dodecane, and 2-methylundecane under high-NOx conditions, in which alkyl proxy radicals (RO2) react primarily with NO, and under low-NOx conditions, in which RO2 reacts primarily with HO2. Experiments were run until 95-100% of the initial alkane had reacted. Particle wall loss was evaluated as two limiting cases using a new approach that requires only suspended particle number-size distribution data and accounts for siz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
153
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(174 citation statements)
references
References 52 publications
(88 reference statements)
17
153
3
Order By: Relevance
“…The determined optimal k w values are consistent with theoretical estimates (SI Appendix, Vapor Wall Loss and Fig. S4) and some observations (11), but larger than some previous observations in the Caltech chamber (18), most likely reflecting the limited time resolution of those observations, which might not have allowed for separation of filling and mixing of the chamber from wall loss, but potentially also reflecting differences between chemical systems.…”
Section: Soa Modeling and The Influence Of Vapor Wall Losssupporting
confidence: 76%
“…The determined optimal k w values are consistent with theoretical estimates (SI Appendix, Vapor Wall Loss and Fig. S4) and some observations (11), but larger than some previous observations in the Caltech chamber (18), most likely reflecting the limited time resolution of those observations, which might not have allowed for separation of filling and mixing of the chamber from wall loss, but potentially also reflecting differences between chemical systems.…”
Section: Soa Modeling and The Influence Of Vapor Wall Losssupporting
confidence: 76%
“…Nonetheless, the known products formed from the photooxidation of these hydrocarbons may provide some insight into the inflammatory responses observed. While there are no prior studies involving pentadecane oxidation products, it is expected that the oxidation products will be similar to those reported in the oxidation of dodecane (i.e., same functionalities with a longer carbon chain; Loza et al, 2014). It is therefore likely that pentadecane oxidation products resemble long chain fatty acids and could potentially insert into the cell membrane (Loza et al, 2014), as previous studies have shown that fatty acids can feasibly insert into the cell membrane bilayer (Khmelinskaia et al, 2014;Cerezo et al, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…While there are no prior studies involving pentadecane oxidation products, it is expected that the oxidation products will be similar to those reported in the oxidation of dodecane (i.e., same functionalities with a longer carbon chain; Loza et al, 2014). It is therefore likely that pentadecane oxidation products resemble long chain fatty acids and could potentially insert into the cell membrane (Loza et al, 2014), as previous studies have shown that fatty acids can feasibly insert into the cell membrane bilayer (Khmelinskaia et al, 2014;Cerezo et al, 2011). This insertion could potentially affect membrane fluidity, which is known to affect cell function substantially although the specific effect depends strongly on the particular modification and cell type of interest (Baritaki et al, 2007;Spector and Yorek, 1985).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The CPOT has been constructed as a complement to the Caltech 24 m 3 batch chambers (Bates et al, , 2016Schilling et al, 2015;Hodas et al, 2015;Loza et al, 2013Loza et al, , 2014McVay et al, 2014McVay et al, , 2016Nguyen et al, 2014Nguyen et al, , 2015Schwantes et al, 2015;Yee et al, 2013;Zhang et al, 2014; in carrying out studies of SOA formation resulting from the oxidation of volatile organic compounds (VOCs) by oxidants OH, O 3 and NO 3 over timescales not accessible in a batch chamber. Due to its steady-state operation, the CPOT also affords the capability to collect sufficient quantities of SOA generated in the reactor for comprehensive composition determination by offline mass spectrometry.…”
Section: Y Huang Et Al: the Caltech Photooxidation Flow Tube Reactormentioning
confidence: 99%